Existence Theorems for Generalized Moment Representations - Holub, A. P.; Голуб, А. П.; Голуб, А. П. (Institute of Mathematics, NAS of Ukraine, 2003)
We establish conditions for the existence of generalized moment representations introduced by Dzyadyk in 1981.